Acceptability and exploratory effects of an occupational therapy intervention to improve recovery and return to work of workers with mental health disorders in primary care: a mixed methods study protocol - Justine Labourot; Justine Labourot; Quan Nha Hong; Quan Nha Hong; Catherine Briand; Catherine Briand; Cynthia Cameron; Marie-José Durand; Marie-José Durand; Nadia Giguère; Nadia Giguère; Élyse Marois; et al. (Frontiers in Psychiatry)
BackgroundPeople with common mental disorders (CMD) are prone to experience work disabilities, which can lead to sick leave. To support their recovery and return to work, evidence recommends providing a combination of primary care services including psychological and work rehabilitation interventions. Furthermore, interventions to coordinate return to work are required to ensure timely access to services and concerted action among stakeholders. Occupational therapists are qualified to provide these interventions and to facilitate sick leave management. However, current medical practices, lack of collaboration among stakeholders, and lack of occupational therapists working within family medicine groups create highly variable care pathways and delays in access to appropriate services.AimThis study aims to evaluate the acceptability and explore the effects of an occupational therapist-led program integrated within family medicine groups designed to improve the management of CMD-related sick leave and promote patients' recovery and sustainable return to work in the Canadian province of Québec.MethodsThis study will consist of a mixed methods multiple case study design. It will also use a participatory research approach, actively engaging family medicine group team members and patient partners throughout the study. The occupational therapy program will include three components: 1) consultation for prevention of sick leave and support for return-to-work decisions, 2) coordination of recovery and return-to-work services, and 3) provision of recovery and work rehabilitation services adapted to each patient’s needs. Questionnaires, interviews, and focus groups will be used to collect data on the eight dimensions of the acceptability model described by Sekhon et al. and to measure pre- and post-outcomes to assess the effects of the occupational therapy program. Data will be analyzed using the Framework Method and repeated measures statistical analysis.DiscussionWe expect that the provision of this innovative occupational therapy program will improve patients’ outcomes and the service trajectory of people with CMD. This study will document how to enhance interprofessional collaboration within family medicine groups and to ensure equitable access to work rehabilitation services for all patients, thereby improving recovery and healthy sustainable return-to-work.